Grundtvig om danskhed og modersmål i 1839. En tale 5. november 1839 - Lundgreen-Nielsen, Flemming (Grundtvig-Studier, 1992)
On Danishness and the Mother Tongue. A Speech by Grundtvig November 5th, 1839 By Flemming Lundgreen-Nielsen In the last half of 1838 Grundtvig delivered a series of lectures on European history from 1788 to the present which gained him the wider public acceptance he for many years had been striving for. In early 1839 some former members of his audience set up a regular society for common citizens dedicated to the promotion of Danishness, Danske Samfund (the Danish Society), with Grundtvig as chairman. The idea was to have conversations and discussions after a short introduction from one of the elected leaders of the club - often Grundtvig himself. Singing songs by Grundtvig and other nationally inclined poets as well as old heroic ballads also helped to create an atmosphere of solidarity and popular and national community. The history of Danske Samfund can be pieced together from the texts of more than 100 introductions which Grundtvig gave, statements by individual members and anonymous police reports on some of the actual sessions. A detailed examination of Danske Samfund has recently been published by the present editor in Dansk Identitetshistorie, III, Copenhagen 1992, p. 31-79. On Tuesday evening of November 5, 1839, Grundtvig in an introduction spoke about his mother tongue. He first claims the historical independence and venerable age of the Danish language, emphasizing its principal difference from Old Norse as well as from a hodge-podge of old Danish and Low German. In his eyes precisely these qualities make the vernacular the only natural means of thinking and feeling for the Danes. Thus the general use of Danish becomes a necessary condition for a thriving culture and national life of the Danish people. Grundtvig continues with an account of his own road to the Danish language. A native Zealander being reared in Jutland, he grew up with the two major Danish dialects, and as a school-boy he on his own read Danish books such as the old chronicle about Holger the Dane. At the university he had to speak Latin and did so (also to evade boredom), but was not permanently tainted by the experience. As a private tutor at the manor house of Egel.kke he resisted the temptation to speak German like the master and the mistress. When at this time he made his d.but as a writer, he clearly favoured Old Norse or Icelandic as the alma mater of Scandinavia and almost considered Danish to be her illegitimate daughter. Following the separation between Denmark and Norway in 1814 he happily realized that he did possess a mother tongue that in fact was nothing but Danish. He recollects this to have occurred in 1816, as he studied the medieval Rhyming Chronicle (printed for the first time in 1495 with several later reprints). Since then he managed to learn to speak and understand spoken English and also became more familiar with the other Scandinavian languages and dialects, and he translated Saxo’s Deeds of the Danes from the Latin, Snorri’s Chronicle of the Norwegian Kings from the Old Norse and the Beowulf epic from the Anglo-Saxon. However, he never doubted that from ancient times Danish is the mother tongue of the Danes. Accordingly he never ceased to regret that those who identify themselves as enlightened and educated persons use the vernacular as if it were a foreign language, not realizing its richness, depth and beauty. It is one of Grundtvig’s declared aims in Danske Samfund to promote the use of the Danish language outside trivial everyday life. In an alternative, but incomplete draught Grundtvig, by way of introduction, mentions a misleading article in a German periodical by a Holstein citizen who claims High German to be an already widespread and ever expanding language in Denmark. Grundtvig’s introduction of Nov. 5, 1839 is another of several retrospective autobiographical interpretations in his works. In this case he concentrates in a deliberately cool and detached manner on his relationship to the Danish language. This was just before the death of Frederik 6. released growing national tensions in the United Monarchy and brought up the burning issue of Danish versus German that finally led to the Schleswig-Holstein war 1848-51.